AERVA JAVANICA MEDIATED SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL EVALUATION OF ZINC OXIDE NANOPARTICLES - G. Afzal; A. Jamal; S. Kiran; G. Mustafa; F. Ahmad; S. Saeed; H. I. Ahmad; S. Dawood (Journal of Animal and Plant Sciences, 2022)
Zinc is an indispensable trace element in the human body. Nano sized zinc-based particles have extensive applications in different fields such as medicine, agriculture and biotechnology. The present study was designed to describe the rapid, simple and environment friendly synthesis of zinc oxide nanoparticles (ZnO NPs) using Aerva javanica. In the current study, biosynthesis and characterization of ZnO NPs using Aerva javanica leaf extract is reported for the first time. Synthesized ZnO NPs were characterized by X-Ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) techniques. Synthesized ZnO NPs were tested against antimicrobial activity using the agar diffusion method. Antibacterial activity of ZnO NPs (10 mg/mL) was measured and zones of inhibition (MIC) against S. aureus and P. aeruginosa were measured as 13.5 mm + 0.8 and 5 + 2.8 mm while ZnO NPs (40 mg/mL) exhibited 18.4 + 4.3 and 8 + 2.8 mm for S. aureus and P. aeruginosa respectively. Antifungal activity of ZnO NPs (10 mg/mL) was measured and MIC against C. albicans and A. niger were recorded as 2.6 mm + 1.7 and 2+ 0.5 mm while ZnO NPs (40 mg/mL) exhibited 6.6 + 2.0 and 2.5 + 0.5 mm for C. albicans and A. niger respectively. Our study concluded that MIC for S. aureus and C. albicans was found to be higher as compared to P. aeruginosa and A. niger. Data analysis showed that ZnO NPs had a significant inhibitory antibacterial effect as compared to antifungal. Thus, present study depicts that the plant extract of A. javanica can be a valuable natural resource to synthesize the functional nanomaterials for targeted applications particularly in molecular medicine.
Keywords: Cholistani shrub; Anti-microbial activity; Aerva javanica; Green synthesis; ZnO Nanoparticles; Molecular-medicine; XRD; FTIR